Understanding Ageing Populations In High-Income Countries: Lesson learned for Indonesia - Sitohang, Marya Yenita (Journal of Indonesian Social Sciences and Humanities, 2023)
Ageing population resulting from the upward trend in life expectancy presents multifaceted issues across all domains, including health, financial, and social aspects. It requires additional public policy intervention to address the challenges and maintain the population well-being during the demographic phenomenon. Using a narrative review, this study delves into the implications of an ageing population in high-income countries like Finland, Germany, and Italy, as well as in Indonesia which is just beginning to experience this transition, and analyse public policies related to ageing population in those countries. The findings highlight several issues related to the ageing population, including health deterioration, housing demand accommodating age-related disabilities, and financial aspects of health insurance and retirement system funding. To address these challenges, high-income countries with ageing populations have implemented various policies. For instance, Finland has established guidelines and funding for elderly healthcare in municipalities, ensuring appropriate medical attention. In addition, pension systems and financial literacy initiatives have been introduced in some countries to support the ageing populace financially. Moreover, home-based geriatric care services in Finland and Germany enable elderly to age comfortably in their own homes. These policy implementations offer valuable insights for countries like Indonesia to better prepare themselves for the social, health, and economic implications associated with an ageing demographic. This comparative analysis serves as a crucial foundation for formulating effective policies tailored to the unique needs of ageing societies worldwide.